Respon Toksisitas Racun Kontak Ekstrak Daun Kipahit Tithonia diversifolia Terhadap Larva Fall Armyworm Spodoptera frugiperda J. E. Smith. (Lepidoptera : Noctuidae) - Dian Dhika; Nurliana Pulungan; Siska Yulianita; Fahri Alamsyah; Faisal Azhari Baldan Panjaitan (Jurnal Media Pertanian, 2026)
Fall Armyworm (FAW) or armyworm (Spodoptera frugiperda J. E. Smith) is an insect native to the United States that is invasive to Indonesia. Pest control can be done with natural/biological compounds derived from plants which are an alternative to chemical insecticides. The purpose of this study was to observe the toxicity response of contact poison extract of Tithonia diversifolia kipahit leaves against S. frugiperda larvae. This study was conducted in the laboratory of the Faculty of Agriculture, Islamic University of North Sumatra, Jl. Karya Wisata Gedung Johor. Medan Johor District, Medan City, North Sumatra, with an altitude of ± 25 m above sea level (meters above sea level) with flat topography. This research was conducted from June 20, 2025 to August 16, 2025. This research used a non-factorial Completely Randomized Design using several treatments, namely k0: control, k1: 0.1%, k2: 0.2%, k3: 0.3%, k4: 0.4%, and k5: 0.5%. By using Analysis using IBM SPSS Statistic 20. Observed parameters S. frugiperda pest level, Lethal concentration LC50 and Lethal Time LT50. The results showed that the administration of kipahit leaf extract (T. diversifolia) using contact poison application in this study had a significant effect on the mortality of S. frugiperda larvae, the highest mortality was at a concentration of k5 (0.5%) which was 77.50%, the higher the concentration of contact poison given, the faster the mortality process of S. frugiperda larvae.